2013
DOI: 10.1093/mnras/stt1400
|View full text |Cite
|
Sign up to set email alerts
|

How cosmic ray electron propagation affects radio–far-infrared correlations in M 31 and M 33

Abstract: We investigate the effect of propagation of cosmic-ray electrons (CRE) on the nonthermal (synchrotron) -far-infrared correlations in M 31 and M 33. The thermal (TH) and nonthermal (NTH) emission components of the radio continuum emission at 1.4 GHz and one higher frequency are compared with dust emission from M 31 and M 33 using Spitzer data. In both galaxies the TH emission is linearly correlated with the emission from warm dust (24 µm, 70 µm), but the power laws of the NTH -FIR correlations have exponents b … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 67 publications
9
67
1
Order By: Relevance
“…The wavelength-dependent distributions (Fig. 12 left) can also be understood as the result of CRE diffusion, as suggested previously by Basu & Roy (2013), Tabatabaei et al (2013a), and Berkhuijsen et al (2013).…”
Section: Propagation Of Cosmic-ray Electronssupporting
confidence: 73%
“…The wavelength-dependent distributions (Fig. 12 left) can also be understood as the result of CRE diffusion, as suggested previously by Basu & Roy (2013), Tabatabaei et al (2013a), and Berkhuijsen et al (2013).…”
Section: Propagation Of Cosmic-ray Electronssupporting
confidence: 73%
“…There is evidence that the assumption does not hold on sub-kpc scales in the Milky Way (Stepanov et al 2014). That equipartition does not hold on small scales is the direct effect of CR diffusion, as was shown for M31 by Berkhuijsen et al (2013). On the other hand, we have just seen that moving from a model with B = 10 µG at all radii to a model with a strong dependence of B on radius had little effect on the spectral index profile.…”
Section: Model With Energy Losses and Varying Magnetic Field Strengthsupporting
confidence: 57%
“…The difference in spectral index is not constant; it varies from 0.08 in the central region of M 51 to 0.16 at around 11 kpc. Berkhuijsen et al (2013) showed that in M 31, unlike other galaxies, most of the CREs are confined to a thin non-thermal disk with an exponential scale height of 0.3 ∼ 0.4 kpc at 1.4 GHz, whereas in M 33 many CREs move out of the thin disk into a thick disk / halo with scale height of ∼2 kpc at 1.4 GHz. It was also found that the diffusion coefficient was ten times greater in M 33 than M 31.…”
Section: Vertical Escape Of Cres By Diffusionmentioning
confidence: 97%
“…The upper bounds of the total energy flux are S ≤ 4.2 × 10 −14 erg cm −2 s −1 (for 3.6 cm) and S ≤ 3.6 × 10 −14 erg cm −2 s −1 (for 20 cm). The magnetic field strength of M33 is B = 8.1 ± 0.5 µG [19]. This large magnetic field strength ensures that the synchrotron radiation dominates the cooling rate of the electron and positron pairs.…”
Section: Radio Observations Of M33mentioning
confidence: 99%